Clay Mineralogy and Petrography of Basal Sand Reservoir of Badin Block, Southern Indus Basin, Pakistan: Implications for Diagenesis and Reservoir Damage Potential Assessment - Sadaf Ismail; Syed Iqbal Mohsin; Syed Kashif Ali Shah; Salman Ismail (International Journal of Economic and Environmental Geology, 2018)
Lower Goru Basal sand reservoirs of Cretaceous age offer a multiple challenge such as subtle migration, microporosity and diagenesis due to its heterogeneity. Petrography, scanning electron microscopic analysis with energy dispersive spectroscopy and x-ray diffractometry analysis on selected core samples show that it contains quartz, which is a major framework detrital grain associated with authigenic kaolinite, illite and chlorite minerals. Quartz overgrowth is the major cementation phase, whereas calcareous cement also occurs occasionally, although, basal sand is classified as quartz arenite. Major diagenetic events recognized in the area include compaction, cementation, dissolution and clay authigenesis. While basal sand is clean quartz rich sand, while presence of labile clays like kaolinite, illite and chlorite may cause problem during drilling and production operations. By maintaining fluid turbulence, drilling with mud of less than 10 pH and using hydrofluoric acid instead of hydrochloric acid in acidizing may help increasing production and reducing drilling operations related problems.